Deasetilasi Kitin Cangkang Rajungan (Portunus pelagicus) Menjadi Kitosan Menggunakan Iradiasi Microwave - Mahardika, Robby Gus; Jumnahdi, Muhammad; Widyaningrum, Yekti (Al-Kimia, 2020)
The crab shell (Portunus pelagis) is still an untapped waste, especially on Bangka Island. Actually, this shell has a high value because there is chitin and chitosan. Chitosan is a biopolymer which has recently been developed into adsorbents, membranes and edible films. The deacetylation process of chitin will be the key to the quality of chitosan produced. Therefore, the purpose of this study is to see the effect of the chitin deacetylation process into chitosan using a microwave. Microwave deacetylation process is carried out with various time variations at 1200 W and 100oC. Characterization and degree of deacetylation (DD) of chitosan crab were analyzed by Fourier Transform Infrared (FTIR) spectroscopy. The results showed that deacetylation using conventional methods for 120 minutes at a temperature 100oC had DD 76.67% while deacetylation using microwave for 40 minutes at a temperature of 100oC had a DD 77.89%. Microwave deacetylation is three times faster than conventional methods.